Rhetorical Move Analysis of Science and Engineering Abstracts Rejected in a Scopus-Indexed Journal - Syifa Fauzia Qurratu’aini; Eri Kurniawan; Arif Husein Lubis (RETORIKA: Jurnal Ilmu Bahasa, 2022)
The role of an appropriate writing of an abstract becomes significantly important as it acts not only as the representative of the whole content of the paper, but also helps journal reviewers to decide whether the article is deemed worthy to be published. While myriad research on rhetorical move analysis of research article abstracts has been conducted, an inadequate amount of them has probed onto rejected research article abstracts, specifically using a cross-disciplinary lens. This study aims to uncover the rhetorical organization and linguistic features of science and sngineering abstracts by utilizing Hyland’s (2000) rhetorical structure. The method of this research is used as the nature of this research rooted from discourse analysis. A total of eighteen rejected abstracts were retrieved from Indonesian Journal of Science and Technology (IJoST). The findings revealed that all of Hyland’s moves were found in both dataset where the move occurrences were identical to one another. However, significant differences existed in step occurrences, particularly in Step 4 of Move 1, Step 1*, 1, and 2 of Move 3, and Step 1 and 2 of Move 5. Engineering studies considered Introduction, Purpose, and Method as obligatory moves, while science studies viewed Purpose as a conventional move of the three. Pattern-wise, science applied two configurations, while engineering used three. Regarding the linguistic features, present tense and active voice were dominant across the disciplines. Furthemore, it was observed that the conventionality of abstract writing had not been properly performed in the rejected abstracts. This research is hoped to provide an insightful source on rejected research article abstracts to future researchers.